2021
DOI: 10.3390/educsci11040153
|View full text |Cite
|
Sign up to set email alerts
|

Correlative Study between Personality Traits, Student Mental Skills and Educational Outcomes

Abstract: The main purpose of this study is determining the correlations between personality traits, academic mental skills and educational outcomes using a quantitative methodology, based on a non-experimental, correlational study. In addition, the following variables are taken into consideration: gender, grade averages and school cycle. The sample is composed of 695 students: these are two institutions (middle and high school) under the provincial direction of Mediouna. In order to gather the information, participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 45 publications
0
4
0
2
Order By: Relevance
“…Neither learners' preferences and styles are tested according the programs nor teaching styles are designed and practiced to match their cognitive desires. Learning styles are attached to individual's personality traits and teaching in line with the learners' expectations enhances their mental skills [11], their level of proficiency [18], and their listening skills [67]. A considerable number of studies has been carried out, and many tools such as self-report surveys, interviews, direct observations, and think-aloud techniques are accessible to investigate the learning styles.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Neither learners' preferences and styles are tested according the programs nor teaching styles are designed and practiced to match their cognitive desires. Learning styles are attached to individual's personality traits and teaching in line with the learners' expectations enhances their mental skills [11], their level of proficiency [18], and their listening skills [67]. A considerable number of studies has been carried out, and many tools such as self-report surveys, interviews, direct observations, and think-aloud techniques are accessible to investigate the learning styles.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Вопрос оценки выраженности психологических особенностей пользователей социальных сетей встает во многих областях исследований: маркетинговых [1,2], управления персоналом [3,4], личностно-ориентированного обучения [5,6], прогнозирования социального поведения [7][8][9], анализа защищенности персонала компаний от социоинженерных атак [10] и др. Данная оценка может проводиться при помощи: тестов-опросников, психодиагностических интервью, рисуночных тестов, ролевых игр, проективных методик и др.…”
Section: Introductionunclassified
“…Knowing that the occupational status is the main characteristic that marks this specific side, it has been shown that the father's occupational status had a significantly stronger impact than the mother's in many countries such us Austria, Germany, Korea, Switzerland, United Kingdom, United States and others (Marks, 2007). Academic performance has a multidimensional character involving a set of psychological (Bouiri, Lotfi & Talbi, 2021), neuroscientific (Elouafi, Lotfi & Talbi, 2021) and chronobiological (Sabaoui, Lotfi &Talbi, 2021) parameters. The latter can be manifested in the impact of the chronotype not only on cognitive aspect, but also on what is psychomotor.…”
Section: Introductionmentioning
confidence: 99%